[1-(Carboxymethyl)cyclohexyl]methanaminium dihydrogen phosphate - Razzaq, Syed Naeem (International Union of Crystallography, 2010)
In the title salt, C(9)H(18)NO(2) (+)·H(2)PO(4) (−), the cyclohexane ring is puckered, the total puckering amplitude Q (T) being 0.555 (4) Å, and an intramolecular N—H⋯O hydrogen bond generates an S(7) ring. In the crystal structure, intermolecular N—H⋯O and O—H⋯O hydrogen bonds lead to R (2) (2)(14), R (3) (3)(8) and R (4) (2)(8) rings, generating a two-dimensional layer.